Depression tendency in physically active senior citizens Tendência a estados depressivos em idosos praticantes de atividade física - Mazo G.Z.* (2005)
The present work identifies cases of depression tendency in physically active senior citizens. In our proposal, the data were collected by interviewing senior members of the Seniority Related Studies Group (GETI/ CEFID-UDESC) using a depression scale method that was adapted from Stoppe e Louzã (1999). To establish the data base 122 candidates with an average age of 68.8 years were included. Most of them (91%) did not show any tendency to depression. On the other hand, the remaining examinees (9%) presented a lack of hope for their own future, leading to an evident condition of depression tendency. Considering the complexity of the factors that are related to depression conditions, physical activities do lead to body, social and mental benefits, reducing the possibility of a depressive state in senior citizens.